HUBUNGAN KONSEP DIRI DENGAN EFIKASI DIRI PADA PASIEN TB PARU DI WILAYAH KERJA PUSKESMAS WONOSARI - Suryalaga, Yogi Ludirta (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
Pulmonary TB and Self Concept are two things that influence each other both directly and indirectly. Pulmonary TB is a disease that affects not only physical health, but also the psychological (mental) and social conditions. At the physical level in the form of self-concept because of daily activities, handling symptoms and treatment. At the psychological level, self-concepts include rejection, worry and stigma about infectious diseases. Physical and emotional conditions determine how a person evaluates his abilities. Self-efficacy in pulmonary TB patients focuses on being able to carry out behaviors that support disease improvement and self-care management such as being able to breathe deeply, cough effectively and adhere to pulmonary TB treatment. This study aims to identify the relationship between self-concept and self-efficacy in pulmonary TB patients in the work area of Wonosari Health Center, Bondowoso Regency. The measuring instrument used was a questionnaire, then bivariate analysis was performed with Spearman Rank Analysis, with a significance of p = 0.05. The results of the Spearman Rank statistical test with significance levels p <0.05. Obtained p value 0.002 which means that Ho is rejected and H1 is accepted, There is a Relationship between Self Concept and Self Efficacy in patients with Pulmonary TB in the Wonosari Health Center work area with a correlation Coefficient level of 0.311. then nurses need to examine the problem of self-concept and self-efficacy to determine appropriate self-concept management interventions and to improve the self-efficacy of pulmonary TB patients and it is expected that future nurses can provide comprehensive nursing care and give more attention to the principle of health promotion through the provision of health education pulmonary TB treatment and provide motivation so that pulmonary TB patients still have the enthusiasm to recover in undergoing treatment to completion.